(untitled) (Historia, 2021)
In 1893 the First Volksraad of the Transvaal Republic (ZAR) decided that wherever possible, "zonen des lands" (sons of the soil) should receive preferential treatment as far as appointments in the civil service were concerned. At that time most government positions were in the hands of Dutch officials and the Afrikaner population felt marginalised. A standpoint was taken to the effect that young Afrikaners were to be appointed, even if it meant that more capable Dutch officials were overlooked. Unfortunately, in the 1890s most of these 'zonen' were ill-equipped to hold responsible positions.